Person-centred planning: an example of best practices in the field of intellectual disability - Araceli Arellano Torres; Feli Peralta López (Universidad de La Rioja, 2015)
At present, the focus of supports in the field of intellectual disability is the individual, with special emphasis on decision-making by users of different services and, therefore, on the need of consultation. In that sense, Person Centered Planning (PCP) becomes an example of best practice that leads the individuals as a central reference, in order to know what is desirable for them and make it possible. This practices requires the professional's participation and involvement, to carry out all the changes that it implies. The purpose of this paper is to present a questionnaire, which is used to assess the perception of professionals on PCP methodology. The results of a pilot study (N = 18) are described, showing the importance of professional's training. An organization that is really committed to this approach, will be more effective if it involves those who have to implement it, providing them training related to this best practice.